Management of Funds in Self-Financing Higher Education Institutions with Special Reference to Business Schools in Kerala - Haseena V. A (Developing Country Studies, 2014)
Education is an important index of human development. Along with economic growth and empowerment, it forms the core of every social and human development doctrines. Among various levels of education, higher education has a pervasive and influential impact on development. Higher education empowers the individual with necessary skills and competence for achieving important personal and social goals and thereby contributing to the social development. It is widely believed that the state of higher education in a country is an index of its future well-being. Education scenario in India is fast changing. In developing countries like ours, government is finding itself incapable to bear the responsibility of higher education as it is already facing acute dearth of resources. Universities and colleges are starved of funds as the support of Govt. is being reduced and grants are not being provided in time causing hardship to them. One of the easier options to overcome the financial crisis in the educational sector is to start self-financing courses. But this alternative is possible only for courses with high demand. Secondly, these courses further strengthen the numerous entry barriers to higher education existing already. Thirdly, the scope for self-financing educational institutions in Kerala is much more limited than for the country as a whole. Fourthly, these institutions cannot evolve as centers of excellence. But, however privatization of higher-level education especially in the field of professional and technical education like Medical, Engineering, Information Technology, Computer, Management, Teacher Education etc. has already commenced